Proteinúria e ácido úrico sérico maternos em pacientes com síndrome de HELLP - Cunha, Hilda Helena Souza da (2012)
Objective: To evaluate the association of maternal serum uric acid (UA) and proteinuria with clinical and demographic data of pregnant women with preeclampsia syndrome (PES) complicated by HELLP syndrome. Methods: One hundred and nine pregnant women were divided into two groups: group 1 - HELLP pregnant women with PES complicated by HELLP syndrome (n=64); group 2 PES pregnant women with PES but no HELLP syndrome (n=105). Results: Age, ethnicity, parity, delivery mode and perinatal mortality were not statistically different between groups. Systolic and diastolic blood pressure, protein to creatinine (P/C) ratio, uric acid, creatinine and maternal complications were statistically different between groups; values were higher and events, more frequent among pregnant women with HELLP syndrome. The newborns of pregnant women with HELLP syndrome were more premature, had a lower birth weight and a lower APGAR score. Conclusion: Uric acid equal to or higher than 6.0 gm/dL and P/C ratio equal to or higher than 5 were more frequent in gestations with HELLP syndrome, which suggests that elevated proteinuria and uric acid levels in pregnant women with PES may increase the chances of developing HELLP syndrome